Braiding Anishinaabe and Western Knowledge Systems to Inform Manomin Restoration on the Upper Winnipeg River - Mehltretter, Samantha L. (Water, 2024)
Elders at Niisaachewan Anishinaabe Nation describe immense cultural, spiritual, economic, and nutritional loss accompanying Manomin (known in English as wild rice) decline on the Upper Winnipeg River. They associate this loss with the installation of hydroelectric dams, increased pollution, and invasive species in the area. This research, in response to Niisaachewan's requests to investigate Manomin decline on the Upper Winnipeg River, demonstrates how Anishinaabe and Western knowledge systems can be braided to inform the restoration of freshwater systems. Methods for braiding knowledge systems were identified through a collaborative scoping review of 138 records that sought to bring Indigenous and Western knowledge systems together in freshwater projects. Two novel frameworks were used to explore principles and practices for braiding knowledge systems in a good way. EAUX (Equity, Access, Usability, and eXchange) is a water themed acronym for important principles when braiding knowledge systems. These principles demonstrate the importance of regarding Indigenous collaborators as equal partners, honoring data sovereignty, centering Indigenous benefit, and prioritizing relationships. The cyclical A-to-A framework (Axiology & Ontology, Epistemology & Methodology, Data Gathering, Analysis & Synthesis, and Application) is used to illustrate how knowledge systems braiding may occur throughout a project. An important finding from the review is the importance of seeking to braid knowledge systems at the values (axiology) and worldviews (ontology) stage before projects are conceptualized. To look at Manomin’s past I drew upon Indigenous research methodologies, lessons from process-based restoration, and Anishinaabe teachings. A novel approach was used to braid Elder oral testimony, government reports, Hudson Bay Company records, newspaper articles, diary entries, historic air photos, and satellite images to identify “good” and “bad” Manomin years. This knowledge was related to Indicators of Hydrologic ...